2016
DOI: 10.21608/jppp.2016.50576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bee Venom Collecting on The Behavior of Honeybee Colonies

Abstract: The present investigation studied bee venom collecting effect on the behavior of honeybee colonies such as (Hygienic and hoarding honeybees behavior, queen right and queen less). Hygienic behavior, the positive effect of using bee venom collection method on hygienic behavior, that increased this behavior (22%) of honey bee worker cells, Apis mellifera,while hoarding behavior in honey bees, Apis mellifera L., statistical analysis that there was no significant difference between before and after treatment in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The early study by Benton et al (1963) highlighted the role of venom collector positions on venom production and they found that using it underneath the brood chamber of honeybee colonies for 5 minutes was not satisfactory to obtain larger quantities of bee venom. Also, Omar et al (1994), El-Saeady et al, (2016 and Omar (2020) used venom collectors at the hive entrance to avoid any harmful effect on honeybee activities inside the colony. Gholamian (2007) used two kinds of venom collector apparatuses one used outside and another inside the hive.…”
Section: Evaluation Of the Effectiveness Of Three Venom Collector Pos...mentioning
confidence: 99%
“…The early study by Benton et al (1963) highlighted the role of venom collector positions on venom production and they found that using it underneath the brood chamber of honeybee colonies for 5 minutes was not satisfactory to obtain larger quantities of bee venom. Also, Omar et al (1994), El-Saeady et al, (2016 and Omar (2020) used venom collectors at the hive entrance to avoid any harmful effect on honeybee activities inside the colony. Gholamian (2007) used two kinds of venom collector apparatuses one used outside and another inside the hive.…”
Section: Evaluation Of the Effectiveness Of Three Venom Collector Pos...mentioning
confidence: 99%
“…The use of natural materials, such as bee venom secreted by honey bee workers, and amino acids extracted from plants to combat diseases and pests of honey bee colonies to obtain honey bee products that are free from harmful substances, such as pesticide residues and antibiotics (5, 10). A bee venom solution was sprayed onto wire cages containing honey bees inside the laboratory, which increased the longevity of workers and improved some characteristics and behaviors, such as hoarding behavior, bee population, brood rearing, pollen storage, and storage of honey, healthy behavior, and foraging activity (6,17,37). Bee venom is a colorless, transparent, viscous liquid that maintains a strong aromatic bitter taste and is an off-white or off-white powder in the dry state.…”
Section: Introductionmentioning
confidence: 99%
“…(34,5,7). Bee venom improves and strengthens the immune system in a manner similar to that of vertebrates, which is necessary for the growth, development, and activity of honeybees (17,1). Feeding with bee venom solution resulted in the longest longevity of honeybee workers (37).…”
Section: Introductionmentioning
confidence: 99%
“…He also found that bees raised without pollen have little and less effective venom in their venom sacs. Therefore, it was recently accepted that venom collection from honey bee colonies using electrical shocks causes a significant decrease in the stored bee bread due to the high consumption of protein within those colonies (Omar, 1994 c;et al, 2006;El-Saeady, et al, 2016;Nowar, 2016;El-Feel 2017;Argena et al, 2021 andBadawy et al, 2022). This reduction in the areas of stored pollen within the colony stimulates a portion of foraging workers to alter their field task and collect pollen or nectar with pollen instead of nectar alone to compensate the reduction.…”
mentioning
confidence: 99%